Efek Limbah Cair Industri Tekstil Pasca IPAL Terhadap Pertumbuhan Tanaman Kubis dan Preferensi Oviposisi Imago Plutella xylostella L. - Siska Rasiska; Muh. Yasin; Syarif Hidayat; Oviyanti Mulyani (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACT Treated industrial textile wastewater has organik and heavy metal compound that have toxicity effect on plant and other organism in agroecosystem. This research aimed to study the effect of industrial textile treated wastewater on cabbage growth and oviposition preference of Plutella xylostella L. The research was done at Green House in Ciparanje, Agriculture Faculty, Universitas Padjadjaran, Jatinangor District, Sumedang, West Java, Indonesia on May to June of 2018. Experimental design used was Block Randomized Design with nine treatments of industrial textile treated wastewater in various concentrations: 0%, 12,5%, 25%, 37,5%, 50%, 62,5%, 75%, 87,5%, and 100%, and three replications. This research revealted that industrial textile treated wastewater has no effect on growth of cabbage, but has an effect on oviposition of Plutella xylostella L. Keyword: industrial textile treated wastewater, growth of cabbage, preference oviposition, Plutella xylostella L.